Reactive oxigen species, essential molecules, during plant - pathogen interactions - Camejoa, Daymi; Guzmán Cedeño, Ángel; Moreno, Alexander (Italia, 2016)
Reactive oxygen species (ROS) are continually generated as a consequence of the normal metabolism in aerobic organisms. Accumulation and release of ROS into cell take place in response to a wide variety of adverse environmental conditions including salt, temperature, cold stresses and pathogen attack, among others. In plants, peroxidases class III, NADPH oxidase (NOX) locates in cell wall and plasma membrane, respectively, may be mainly enzymatic systems involving ROS generation. It is well documented that ROS play a dual role into cells, acting as important signal transduction molecules and as toxic molecules with strong oxidant power, however some aspects related to its function during plant-pathogen interactions remain unclear. This review focuses on the principal enzymatic systems involving ROS generation addressing the role of ROS as signal molecules during plant-pathogen interactions. We described how the chloroplasts, mitochondria and peroxisomes perceive the external stimuli as pathogen invasion, and trigger resistance response using ROS as signal molecule.
Keywords: PLANT PHYSIOLOGY AND BIOCHEMISTRY; PEROXIDASAS; ORGANULOS; ESTRES BIOTICO